Optimasi Rute Pengiriman Produk dengan Meminimumkan Biaya Transportasi Menggunakan Metode Saving Matrix di PT. DEF - Fatimah Juma Sesa; Hendra Syarifudin; Yusmet Rizal (UNIVERSITAS NEGERI PADANG, 2019)
Abstract – The route of transportation is a solutions in minimizing the costs of distribution. Saving Matrix method is a method in Vehicle Routing Problem (VRP) that used to get efficient routes. The use of this method is by combining the points goals that have the greatest distance saving and paying attention to the volume of requests of each objective. Then performing visits in order by vehicle so that efficient delivery route obtained. In this paper, it is discussed the application of Saving Matrix method in determination routes of delivery product at company DEF. In the end of the work, it was found that this method gives less route than initial route of six routes into five routes. In Month, gotten savings distance 105 km or about 14%, savings fuel 21 liters or about 14% so the use of the vehicle is reduced meaning a magnitude can minimizing cost.Keywords – Transportation, Route, Saving Matrix, VRP (Vehicle Routing Problem)